Effect cadmium on germination, seedling growth and metal contents of sunflower (Helianthus annus L.) - Aycicek, Mehmet; Kaplan, Olcay; Yaman, Mehmet (Asian Journal of Chemistry, 2008)
In this study. sunflower plants were grown by using the cadmium-added irrigation water at different concentrations. Increasing cadmium applications in irrigation water caused a decrease at dry weight in third week of the study. Cadmium concentration in shoot samples increase depending on cadmium in irrigation water while a stationary change was found in cadmium level of root samples after irrigation with 0.05 mg L-1 cadmium. As similar cadmium in shoot, iron in root samples increase by all cadmium dozes. Furthermore, a stationary change in iron of shoot and zinc of both root and shoot were found for all doses and weeks.
Keywords: cadmium; sunflower; metal; irrigation water; plant seedling